Cost-Effectiveness and Feasibility of Anemia Management in Pregnant Women: A Systematic Review - Della Winanti; Isra Yanti; Nurul Fitriyah; Sirajul Munira; Mufdlillah Mufdlillah; Firdaus Hafidz (Media Kesehatan Masyarakat Indonesia, 2025)
Anemia among expectant mothers is a major health issue worldwide, especially in developing countries, where prevalence reaches 37%. Various interventions, such as micronutrient supplementation and intravenous iron administration, have been widely implemented. However, limited systematic reviews have comprehensively evaluated both the cost-effectiveness and feasibility of such interventions in low- and middle-income countries (LMICs). This study aims to systematically evaluate recent evidence on the feasibility and cost-effectiveness of anemia management interventions for pregnant women in developing countries. The review followed the 2020 PRISMA guidelines and was registered in PROSPERO (CRD420251089753). Article searches were conducted across five primary databases (CINAHL, CENTRAL, PubMed, Wiley, and Taylor & Francis) for publications between 2015 and 2025. Study selection was performed independently by six authors. Seven studies meeting the inclusion criteria were analyzed narratively. The findings indicated that interventions such as Multiple Micronutrient Supplementation (MMS) and Intravenous Iron Sucrose (IVIS) were highly cost-effective, demonstrating Incremental Cost-Effectiveness Ratios (ICERs) substantially lower than the willingness-to-pay threshold (USD 653–1,792 per DALY) in developing nations, including Indonesia. Feasibility of implementation was influenced by healthcare system capacity, logistical resources, educational initiatives, and sociocultural contexts. Overall, MMS and IVIS interventions demonstrated superior efficiency and effectiveness compared to conventional therapies, though their success relies on system readiness and contextual adaptation. This review fills a critical evidence gap by jointly assessing cost-effectiveness and real-world feasibility, providing a strong foundation for designing sustainable, evidence-based strategies to manage anemia in resource-limited settings.